Children's Privacy and Standard Clauses in Digital Services: A Substantive Justice Analysis - Masturi, Frida Nurrahma; Listyani, Ajeng Aditya; Agus Mardianto (Jurist-Diction, 2026)
The development of digital technology has made children active users of online services vulnerable to privacy violations due to standard clauses unilaterally drafted by service providers. This study aims to analyze the application of the principle of substantive justice in assessing standard clauses and forms of legal protection for children's privacy in the digital era. Using normative juridical methods and a conceptual approach, this study examines national regulations and international instruments related to child data protection. The results show that although Indonesia has a legal basis through the Child Protection Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law, its implementation has not been effective due to weak oversight and the absence of age verification mechanisms and parental consent. Strengthening regulations based on substantive justice, the establishment of independent oversight bodies, and improving digital literacy are needed to realize fair and sustainable protection of children's privacy.